USING QUESTIONS EFFECTIVELY AS A TEACHING DEVICE - Rahman, Ali Wira (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
English teaching is a process that the teacher interacts with students. Asking and answering are the primary ways to communicate with each other, so questioning plays a central role in classroom. It urges students to think actively and develops their creative thinking. Because of the importance of questions to the research process, one of the things a teacher at a university tries to teach students is how to ask good questions, and how to answer them appropriately. This makes the process of questioning important in every class taught at a university. Questions are important to the students in a class for two reasons: (1) Students learn to ask questions by asking questions. Students learn to ask good questions by asking questions and then receiving feedback on them. Students learn to become scholars by learning to ask good questions; (2) student asking a question is at that moment a self-motivated learner - a researcher. This is the behavior trying to nurture